Quantitative Analysis of Emtricitabine in Dosage Forms Using Green RP-HPTLC and Routine NP-HPTLC Methods—A Contrast of Validation Parameters - Alam, Prawez (ACS Omega, 2020)
[Image: see text] In this research, an antiviral drug emtricitabine (ECT) was quantified using the validated green reversed-phase high-performance thin-layer chromatography (RP-HPTLC) and routine normal-phase HPTLC (NP-HPTLC) methods in the marketed oral solutions and capsules. Green RP-HPTLC-densitometry quantification was performed using the acetone/water (70:30, v/v) solvent system as the mobile phase. Routine NP-HPTLC-densitometry quantification was performed using the chloroform/methanol (85:15, v/v) solvent system as the mobile phase. The detection was performed at λ(max)—285 nm for both of the methods. Both densitometry methods were validated for different parameters. Most of the validation parameters including linearity, precision, accuracy, detection, and quantification limits for the green densitometry method were found to be superior compared to the routine densitometry technique. The ECT contents of commercial oral solution and commercial capsules were found to be 100.85 and 98.27%, respectively, using the green densitometry technique. The ECT contents of oral solutions and capsules were 97.16 and 95.54%, respectively, using the routine densitometry technique. Accordingly, the green densitometry technique was found to be better than the routine densitometry technique for ECT assays. Thus, the green densitometry technique can be successfully applied for the quantitation of ECT in the marketed formulations.